Computer-aided Design for Robotic Assembly Technology - Nevlyudov, I. Sh.; Tsymbal, O. M.; Milyutina, S. S. (ХНУРЭ, 2009)
There is proposed the logical model of assembly technological processes design. The basic set of predicates, which characterizes the assembly process, is considered. The model is implemented by Prolog language program. The models of technological process design, based on semantic nets and on frames and a method of voice information input are proposed. Also the questions of decision-making for robot manipulations are considered.
Keywords: predicate; robotics; logics; assembly